Fungos micorrízicos arbusculares e Azospirillum brasilense no desenvolvimento de sorgo e milho cultivados em solo contaminado com cobre - Barros, Sinara (2022)
Copper is an essential element for the development of vegetables, but in excess it becomes a major problem for the environment. Some plants are able to tolerate abiotic stresses, including those caused by copper and other heavy metals, in addition, some microorganisms such as fungi and bacteria can help plants to develop in contaminated environments. Therefore, the general objective of this work was to analyze the effect of arbuscular mycorrhizal fungi and Azospirillum brasilense on the development and tolerance of sorghum and corn grown in soil contaminated with copper. Three studies were carried out, the first of which aimed to determine the influence of Azospirillum brasilense inoculation on the development and tolerance to copper in maize and sorghum plants, the second was to analyze the behavior of mycorrhizal fungi in the growth and development of corn and sorghum in soil contaminated with copper and the third to analyze the effect of co-inoculation between mycorrhizal fungi and Azospirillum brasilense on corn and sorghum in soil contaminated with copper. The results show that the aerial and root parts of maize and sorghum plants are reduced at high concentrations of copper in the soil. The bacterium Azospirillum brasilense increases the development of corn and sorghum and the tolerance of plants in soil contaminated with copper and decreases the translocation of the metal to shoots and grain. Inoculation of mycorrhizal fungi increases the bioconcentration factor and tolerance index of corn and sorghum to copper. Maize was more responsive to mycorrhizal colonization in roots with the species Acaulospora scrobiculata. Inoculation of Acaulospora scrobiculata promotes greater root dry mass, root volume and mycorrhizal colonization of sorghum in soil contaminated with copper. Inoculation of Acaulospora scrobiculata and co-inoculation with Azospirillum brasilense increase root dry mass, root volume, corn leaf area in soil not contaminated with copper. Inoculation with Acaulospora scrobiculata and co-inoculations of mycorrhizal fungi with Azospirillum brasilense reduce the copper content in shoots and roots of sorghum plants.